2016
DOI: 10.21873/anticanres.11160
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the PI3K/PTEN/AKT/mTOR Pathway in Treatment of Sarcoma Cell Lines

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…Musculoskeletal sarcomas, including OS, commonly develop aberrant activation of the PI3K/Akt signaling pathway [24]. Moreover, targeting the PI3K/Akt signaling pathway can be an approach for the treatment of sarcomas [25]. Zhang et al [26] also found that inhibiting the PI3K/Akt pathway suppressed the progression of Ewing sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal sarcomas, including OS, commonly develop aberrant activation of the PI3K/Akt signaling pathway [24]. Moreover, targeting the PI3K/Akt signaling pathway can be an approach for the treatment of sarcomas [25]. Zhang et al [26] also found that inhibiting the PI3K/Akt pathway suppressed the progression of Ewing sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Components of the PI3K/Akt/mTOR signaling pathway are commonly upregulated in malignant tumors, and increased Akt phosphorylation is commonly observed ( 19 ). The activation of Akt signaling is associated with cell proliferation, migration and invasion ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ligand binding initiates several signalling cascades involving cell growth, proliferation, apoptosis and autophagy [10,11] (Figure 1). The major signal transduction pathways are: ras/raf/mitogen activated protein kinase (MAPK), phosphoinositide 3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) and Janus kinase/signal transducer and activator of transcription (JAK/STAT) [12][13][14][15], all of which promote cell survival [16]. We and others have reported that EGFR was overexpressed in many types of osteosarcomas and STSs [9,11,17].…”
Section: Research Papermentioning
confidence: 99%
“…An extensively studied downstream pathway of EGFR is the PI3K/AKT/ mTOR pathway, critically involved in the regulation of cell apoptosis [27], autophagy [10], proliferation [12,28] and metabolism [29]. Dysregulation of this pathway plays a major role in many different cancers [30,31].…”
Section: Research Papermentioning
confidence: 99%